Identifying immune checkpoints on dysregulated T-cells as prognostic biomarkers for multiple myeloma patients with COVID-19 - Li, Ziping; He, Huiwen; Zhang, Fujing; Li, Haolong; Jin, Xianghong; Song, Yuhang; Liu, Shuangjiao; Wang, Xuan; Zhuang, Junling (Frontiers in Immunology, 2024)
Background: Broad T cell phenotypic alterations and potential dysfunctions were prominent in COVID-19. There are few and inconclusive data about the role of immune checkpoints for T cell exhaustion/activation during SARS-CoV-2 infection in multiple myeloma (MM) patients.Methods: We tested T cell subsets and immune checkpoints in 177 MM patients with COVID-19, as well as in 32 healthy infected controls and 42 uninfected MM patients. The percentage of CD4+ and CD8+ subpopulation and immune checkpoints (PD-1, TIGIT, TIM-3, LAG-3, CTLA-4, OX40, and 4-1BB) were evaluated by flow cytometry.Results: We have found that pronounced lymphopenia and inverted CD4/CD8 ratio in severe COVID-19 patients were especially developed within the first month after infection. And T cell subset dysregulation was persistent in severe patients recovering from SARS-CoV-2 infection. Immune checkpoints on CD4+ T cells were variable and uncorrelated with the level of adaptive immunity, while the proportion of CD4+ T cells was positively correlated with humoral immune response. PD-1 and TIGIT on CD8+ T cells were significantly elevated in severe patients and sustained for more than 2 months, which was associated with impaired cellular immune function. Moreover, exhausted molecules PD-1 and TIGIT on T cells were reduced in immunotherapy patients.The prolonged T cell dysregulation after severe SARS-CoV-2 infection highlights the close surveillance from reinfection in MM patients even during convalescence. PD-1 and TIGIT on CD8+ T cells could be important prognostic factors to stratify prognosis in MM patients with COVID-19. Moreover, immunotherapy may downregulate the expression of exhausted checkpoints PD-1 and TIGIT, leading to T cell overactivation and severe COVID-19.